Analysis of Mechanism and Implementation of Murabahah Contract in Oto iB Hasanah Financing (Study at BNI Syariah Banda Aceh) - Fakrurradhi Fakrurradhi; Saparuddin Siregar; Sugianto Sugianto (Budapest International Research and Critics University, 2022)
This study aims to analyze the mechanism and application of consumptive financing contracts in the Oto iB Hasanah BNI Syariah Banda Aceh product. This research is a research (field research) using a descriptive qualitative method with a phenomenological approach.The results of the analysis concluded that technically the mechanism and application of consumptive financing on the Oto iB Hasanah BNI Syariah Banda Aceh product in three stages, namely: First, the customer applies for consumptive financing for the Oto iB Hasanah BNI Syariah Banda Aceh product by completing the file requested by BNI Syariah, second, checking data or data verification for the completeness and correctness of the file, third, field survey with 5C principles (Character, Capacity, Capital, Condition and Collateral). And the murabahah contract on consumptive financing for the Oto iB Hasanah BNI Syariah product is in accordance with the fatwa of the National Sharia Council and the Indonesian Ulema Council No: 04/ DSN-MUI/IV/2000 and practiced using murabahah financing indicators, namely an agreement on profit with BNI Syariah bank transparency with customers who take Oto iB Hasanah products, clear payment methods, sale and purchase agreements and direct delivery of goods by the bank.